Digital Supply Chain Model for Higher Certificate Management in Thailand - Artaphon Chansamut (International Journal of Supply Chain Management, 2022)
The purpose of research study were to study and to evaluate digital supply chain model for higher certificate management in Thailand. The samples in the research study consisted of ten purposively selected experts consisted of five experts on supply chain management, five experts on Digital Technology, Data were analysed by arithmetic mean and standard deviation. The research findings model seven elements namely main components, Supplier, Organization ( Manufacturer, Finished product, Customers Satisfaction and Feedback. The ten experts agree that digital supply chain model for higher certificate management in Thailand was high suitability that show the model is appropriate and applicable to real practice.